Dreaming of a Learning Task Is Associated with Enhanced Sleep-Dependent Memory Consolidation - Wamsley, Erin J.; Tucker, Matthew; Payne, Jessica D.; Benavides, Joseph A.; Stickgold, Robert (Current biology, 2010)
It is now well established that postlearning sleep is beneficial for human memory performance [ 1–5]. Meanwhile, human and animal studies have demonstrated that learning-related neural activity is re-expressed during posttraining nonrapid eye movement (NREM) sleep [ 6–9]. NREM sleep processes appear to be particularly beneficial for hippocampus-dependent forms of memory [ 1–3, 10]. These observations suggest that learning triggers the reactivation and reorganization of memory traces during sleep, a systems-level process that in turn enhances behavioral performance. Here, we hypothesized that dreaming about a learning experience during NREM sleep would be associated with improved performance on a hippocampus-dependent spatial memory task. Subjects were trained on a virtual navigation task and then retested on the same task 5 hr after initial training. Improved performance at retest was strongly associated with task-related dream imagery during an intervening afternoon nap. Task-related thoughts during wakefulness, in contrast, did not predict improved performance. These observations suggest that sleep-dependent memory consolidation in humans is facilitated by the offline reactivation of recently formed memories, and furthermore that dream experiences reflect this memory processing. That similar effects were not observed during wakefulness suggests that these mnemonic processes are specific to the sleep state. ►Improved spatial memory performance is predicted by task-related dream experience ►Task-related thoughts during waking are unrelated to memory performance ►Findings are discussed in light of models of sleep-dependent memory consolidation